Process design of patchouli oil distillation by varying operating conditions to increase yields of patchouli oil - . Harunsyah; M. Yunus (Syiah Kuala University, 2012)
Patchouli oil is part of the essential oils obtained from patchouli plants by distillation. Patchouli oil is widely used in industry as provider of aroma and flavour. Quality of patchouli oil is determined by its natural characteristics and foreign materials contain in the patchouli oil. The foreign materials contain in the patchouli oil can be damage the quality of patchouli oil. Aceh Province is the largest contribute in producing patchouli oil in Indonesia. Patchouli oil processing areas in the Aceh region, precisely in the North Aceh and South Aceh district. In generally farmer of patchouli in Aceh is traditional farmer and many of them not yet follow the best refine system. They do it base of previously experience. Refinery equipment that used from former drum that can be reaction with patchouli oil, with the result can to change chemistry structure of patchouli oil, so that the oil produced is dirty and has dark colour and does not meet the specified quality requirements). The main purpose of this research is to increase yield and the quality of patchouli oil by using of refinery equipment modification process to meet quality standards. In this research the former drum is replaced by stainless steel drum. Method of test quality and procedure of test quality same as standard method of SNI-06-2385-2006. The results showed that the using of refinery equipment (stainless steel drum) able to increase the yield and oil quality, especially in terms of colour, physicochemical properties and concentration of its main components and also meet the quality requirements of national standards